Enabling Angioplasty‐Ready “Smart” Stents to Detect In‐Stent Restenosis and Occlusion - Chen, Xing (Adv Sci (Weinh), 2018)
Despite the multitude of stents implanted annually worldwide, the most common complication called in‐stent restenosis still poses a significant risk to patients. Here, a “smart” stent equipped with microscale sensors and wireless interface is developed to enable continuous monitoring of restenosis through the implanted stent. This electrically active stent functions as a radiofrequency wireless pressure transducer to track local hemodynamic changes upon a renarrowing condition. The smart stent is devised and constructed to fulfill both engineering and clinical requirements while proving its compatibility with the standard angioplasty procedure. Prototypes pass testing through assembly on balloon catheters withstanding crimping forces of >100 N and balloon expansion pressure up to 16 atm, and show wireless sensing with a resolution of 12.4 mmHg. In a swine model, this device demonstrates wireless detection of blood clot formation, as well as real‐time tracking of local blood pressure change over a range of 108 mmHg that well covers the range involved in human. The demonstrated results are expected to greatly advance smart stent technology toward its clinical practice.